Use of nalidixic acid for constructing the replication map of the Mycobacterium phlei chromosome - Konícek, J; Konícková-Radochová, M; Cáslavská, J; Wolf, A (Folia microbiologica, 1981)
Nalidixic acid was used for describing more accurately the terminal replication region of the Mycobacterium phlei chromosome. Cell division in synchronized cultures was not sensitive to this acid any more between 185-190 min, i.e. about 10 min after replication of the ser gene, the last of 24 genes of the replication map described so far. The replication of the chromosome was controlled by determining the position of the bac gene. Microscopic studies in phase contrast of the cells that were subjected for long time periods to nalidixic acid treatment at a bactericidal concentration showed elongated cells. The electronmicroscopic observation showed that a portion of the population influenced by nalidixic acid lyses, whereas other cells remain intact and resemble control cells.
Keywords: replikace DNA; Chromosomes, Bacterial; Chromosome Mapping; buněčné dělení; kyselina nalidixová; Cell Division; mapování chromozomů; DNA, Bacterial; Nalidixic Acid; bakteriální chromozomy; Mycobacterium phlei; Mycobacterium; DNA Replication; DNA bakterií